Intraventricular Rituximab in Pediatric CD20-positive Refractory Primary Central Nervous System Lymphoma. Issue 7 (October 2019) - Wada-Shimosato, Yuko; Ikeda, Junji; Tsujimoto, Shin-ichi; Sasaki, Koji; Yanagimachi, Masakatsu; Kajiwara, Ryosuke; Shiba, Norio; Murata, Hidetoshi; Kawahara, Nobutaka; Yamanaka, Shoji; Tanoshima, Reo; Ito, Shuichi
Abstract : Primary central nervous system lymphoma (PCNSL) is a rare and aggressive type of extranodal non-Hodgkin lymphoma that carries an unsatisfactory prognosis. Treating refractory PCNSL is challenging because of resistance to conventional cytotoxic and intrathecal chemotherapies. Therefore, novel therapeutic approaches are needed. Here, we report a 12-year-old boy with CD20-positive PCNSL, which was refractory to combination chemotherapy and intravenous rituximab. However, the patient achieved complete remission after repeated intraventricular rituximab administration. The results of this case indicate that intraventricular rituximab is an effective option to treat refractory PCNSL in children.